2020
DOI: 10.21203/rs.3.rs-35388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and pathological findings of SARS-CoV-2 infection and concurrent IgA nephropathy: A case report

Abstract: Background: Since the Coronavirus Disease 2019 (COVID-19) outbreak, there is limited data on the clinical characteristics, treatment strategies and prognosis of COVID-19 in patients with concurrent renal disease. The kidney is believed to have a predisposition for COVID-19 due to its abundant angiotensin-converting enzyme 2 (ACE2) expression, which acts as a cell entry receptor for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Recent postmortem investigations reveal renal involvement in COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…She received a renal biopsy, which showed 2+ IgA mesangial deposits. Additionally, ultra-structural study showed electron-dense immune-type deposits in the mesangial area, while, there was no evidence of viral particles in the glomeruli (24). Similarly, Sharma et al reported two COVID-19 positive African American patients who developed acute renal impairment and proteinuria.…”
Section: High-risk Apol1 Genotype and Covid-19-associated Collapsing mentioning
confidence: 95%
“…She received a renal biopsy, which showed 2+ IgA mesangial deposits. Additionally, ultra-structural study showed electron-dense immune-type deposits in the mesangial area, while, there was no evidence of viral particles in the glomeruli (24). Similarly, Sharma et al reported two COVID-19 positive African American patients who developed acute renal impairment and proteinuria.…”
Section: High-risk Apol1 Genotype and Covid-19-associated Collapsing mentioning
confidence: 95%